The Great Umar Khayyam A Global Reception of the Rubáiyát - Seyed-Gohrab, A.A (Iranian Studies Series, 2012)
The Rubáiyát by the Persian poet 'Umar Khayyæm (1048-1131) is used in contemporary Iran as a resistance literature, symbolizing the secularist voice in cultural debates. While Islamic fundamentalists criticize Khayyæm as an atheist and materialist philosopher who questions God's creation and the promise of reward or punishment in the hereafter, secularist intellectuals see in him an example of a scientist who scrutinizes the mysteries of the world. Others see a spiritual master, a Sufi, who guides people to the truth. This volume collects eighteen essays on the history of the reception of 'Umar Khayyæm in various literary traditions, exploring how his philosophy of doubt, carpe diem, hedonism, and in vino veritas has inspired generations of poets, novelists, painters, musicians, calligraphers and film-makers.